Implantation of a Newly Designed Supratarsal Gold Weight versus the Traditional Pretarsal Model for the Correction of Long-standing Paralytic Lagophthalmos: A Retrospective Cohort Study - Lailaksiri, Natthiya; Wanichsetakul, Pawarit; Saonanon, Preamjit (Archives of Plastic Surgery, 2024)
Background The study determined to compare the clinical outcomes of traditional gold weight implantation for the correction of paralytic lagophthalmos with those of a newly designed model.Methods In this retrospective cohort study, we enrolled 30 patients (76% females; average age 60.8 ± 12 years) with facial palsy who underwent implantation of either the traditional pretarsal gold weight (PT group; n = 15) or a new supratarsal model (ST group; n = 15) from May 2014 to April 2019. The main outcome measures were the 12-month postoperative weight prominence, weight migration, improvement of lagophthalmos, upper eyelid contour, and upper eyelid ptosis. The secondary outcome was long-term (24 months) reoperative rate.Results The new model group had significantly better eyelid contour (risk ratio [RR] 3.16, 95% confidence interval [CI] 1.62–6.15, p = 0.001), less weight prominence (RR 1.74, 95% CI 1.13–2.70, p = 0.013), less weight migration (RR 1.31, 95% CI 1.12–1.54, p = 0.001), and less eyelid ptosis (RR 2.36, 95% CI 1.21–4.59, p = 0.011) than the traditional model group. Improvement of lagophthalmos was not statistically significant between the two groups (RR 1.44, 95% CI 0.72–2.91, p = 0.303). The 24-month reoperative rate was 53.3% in the PT group versus 13.3% in the ST group (RR 2.00, 95% CI 1.15–3.49, p = 0.015).Conclusion The newly designed supratarsal gold weight showed superior postoperative outcomes than the standard traditional model.
Keywords: lagophthalmos; facial palsy; lid load; gold weight implantation; supratarsal implantation